CONTEMPORARY THEORIES OF LEADERSHIP WITH THE CHALLENGES FOR THE LEADER’S PERFORMANCE - de Campos Schubert Ribeiro, Regilaine (Revista Gênero e Interdisciplinaridade, 2023)
The purpose of this article is to present the results of a study that delved into the challenges of leadership development in contemporary times. The study had two specific objectives: to investigate key themes for leadership development in the current context of companies and organizations and to identify emerging trends, challenges and new themes around the topic of leadership. The article makes use of a literature review that covers studies on the subject, emphasizing the main theoretical, methodological and conceptual approaches. The study also identifies the necessary attributes of competent leadership styles needed to respond to the current business and organizational context. In addition, it highlights new challenges and concerns related to the topic of leadership. Study results provide valuable insights into the issues and challenges faced by business leaders, which can be used to develop new research agendas and approaches in the field.